Supported La2O3 and MgO Nanoparticles as Solid Base Catalysts for Aldol Reactions While Suppressing Dehydration at Room Temperature. Issue 2 (5th September 2012) - Frey, Anne Mette; Karmee, Sanjib Kumar; de Jong, Krijn Pieter; Bitter, Johannes Hendrik; Hanefeld, Ulf
Abstract La2O3 and MgO nanoparticles (3–4 nm) supported on carbon nanofibers were evaluated as solid base catalysts for the aldol reaction of benzaldehyde and acetone at room temperature. Both catalysts were found to be highly active and selective with respect to 4‐hydroxy‐4‐phenylbutan‐2‐one, thus suppressing the elimination of H2O, which is a challenge for this reaction. La2O3 nanoparticles were more stable towards water, which makes them more applicable than MgO nanoparticles as a solid base catalyst for this reaction.